A long ether chain thiophene copolymer and its preparation method and application

By inserting 3-(2-butoxyethyl)thiophene segments into P3HT, a long ether chain thiophene copolymer is solved, and the problem of poor contact between P3HT and perovskite is significantly improved. Energy conversion efficiency.

CN119039575BActive Publication Date: 2025-02-18CHAIN WALKING NEW MATERIAL TECHNOLOGY (GUANGZHOU) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411519568.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-18
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

In the prior art, poly3-hexylthiophene (P3HT) as a hole transport layer has physically poor contact with the perovskite interface in perovskite solar cells, resulting in carrier recombination and voltage and current loss, affecting energy conversion. efficiency.

Method used

Using ether chain thiophene copolymer, the molar percentage of the copolymer is increased by inserting 3-(2-butoxyethyl)thiophene segments into P3HT to form random copolymers to improve the interface between P3HT and perovskites. Contact.

Benefits of technology

It effectively reduces charge recombination in the device, improves the photoelectric conversion efficiency of perovskite solar cells, and improves the solubility and processability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119039575B_ABST
    Figure CN119039575B_ABST
Patent Text Reader

Abstract

The invention discloses a long ether chain thiophene copolymer and a preparation method and application thereof. The long ether chain thiophene copolymer is a copolymer of 3-hexylthiophene and 3-(2-butoxyethyl)thiophene, wherein the molar percentage of the 3-(2-butoxyethyl)thiophene chain segment in the long ether chain thiophene copolymer chain segment is 4.7% to 20%. The insertion rate of 3-(2-butoxyethyl)thiophene in the long ether chain thiophene copolymer is high. The copolymer is applied to a perovskite device, can effectively improve the problem of physical poor contact between P3HT and the perovskite interface, reduce charge recombination in the device, and further effectively improve the photoelectric conversion efficiency of the perovskite solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thiophene copolymers, and in particular to a long ether chain thiophene copolymer and a preparation method and application thereof. Background Art

[0002] Single-junction perovskite solar cells (PSCs) have achieved power conversion efficiencies (PCEs) of 26% and are considered an important resource for next-generation photovoltaic cells due to their low-cost fabrication process and attractive optoelectronic performance.

[0003] Perovskite solar cells generally include a fluorine-doped tin oxide (FTO) conductive substrate, an electron transport layer, a perovskite photosensitive layer, a hole transport layer and a counter electrode. The hole transport layer extracts and transports holes, which plays an important role in improving the energy conversion efficiency of perovskite solar cells.

[0004] Poly (3-hexylthiophene) is a derivative of polythiophene, which has good stability and solution coating performance, and has unique photoelectric properties and high hole transport performance. Therefore, poly (3-hexylthiophene) (P3HT) has become one of the most commonly used polymer hole transport materials. However, the efficiency of perovskite solar devices prepared using P3HT alone as a hole transport layer is not ideal. The main reason is that there is a physical poor contact between P3HT and the perovskite interface, which will cause serious recombination of carriers, resulting in significant voltage and current losses, thereby affecting the energy conversion efficiency of perovskite solar cells. Therefore, it is an urgent problem to modify P3HT, improve the contact between the polymer and the perovskite interface, and then improve the energy conversion efficiency of perovskite solar cells. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects and shortcomings of the prior art and provide a long ether chain thiophene copolymer. The insertion rate of 3-(2-butoxyethyl)thiophene in the long ether chain thiophene copolymer of the present invention is high. The copolymer is applied to perovskite devices, which can effectively improve the problem of poor physical contact between P3HT and the perovskite interface, reduce charge recombination in the device, and thus effectively improve the photoelectric conversion efficiency of the perovskite solar cell.

[0006] The object of the present invention is to provide a long ether chain thiophene copolymer, which is a copolymer of 3-hexylthiophene and 3-(2-butoxyethyl)thiophene, wherein the molar percentage of the 3-(2-butoxyethyl)thiophene segment in the long ether chain thiophene copolymer segment is 4.7% to 20%.

[0007] In some embodiments of the present invention, the molar percentage of the 3-(2-butoxyethyl)thiophene chain segment in the long ether chain thiophene copolymer chain segment is 4.7% to 8.3%.

[0008] In some embodiments of the present invention, the molar percentage of the 3-(2-butoxyethyl)thiophene chain segment in the long ether chain thiophene copolymer chain segment is 16% to 20%.

[0009] In some embodiments of the present invention, the long ether chain thiophene copolymer is a random copolymer.

[0010] In some embodiments of the present invention, the structure of the long ether chain thiophene copolymer is shown in formula (I):

[0011]

[0012] Formula (I)

[0013] Wherein, the number average molecular weight of the long ether chain thiophene copolymer is 6.5~8.9KDa.

[0014] In some embodiments of the present invention, the HT value of the long ether chain thiophene copolymer is ≥90%, and the PDI is ≥2.5.

[0015] Another object of the present invention is to provide a method for preparing a long ether chain thiophene copolymer, comprising the following steps:

[0016] Under the catalysis of palladium catalyst, 2-bromo-3-(2-butoxyethyl)thiophene and 2-bromo-3-hexylthiophene react to obtain the long ether chain thiophene copolymer.

[0017] In some embodiments of the present invention, the palladium catalyst is selected from diimine palladium catalysts.

[0018] In some embodiments of the present invention, the structure of the diimine palladium catalyst is as follows:

[0019] .

[0020] In some embodiments of the present invention, the molar ratio of 2-bromo-3-(2-butoxyethyl)thiophene to 2-bromo-3-hexylthiophene is 1-5:15-19.

[0021] In some embodiments of the present invention, the ratio of the total mole of 2-bromo-3-(2-butoxyethyl)thiophene and 2-bromo-3-hexylthiophene to the mole of the palladium catalyst is 1:0.001-0.01.

[0022] In some embodiments of the present invention, the reaction temperature is 80-120° C. and the reaction time is 12-36 hours.

[0023] In some embodiments of the present invention, the reaction further contains an inorganic base, an organic acid and a solvent.

[0024] In some embodiments of the present invention, the inorganic base includes at least one of potassium carbonate and sodium carbonate.

[0025] In some embodiments of the present invention, the organic acid includes at least one of pivalic acid and caproic acid.

[0026] In some embodiments of the present invention, the solvent includes N,N-dimethylacetamide.

[0027] In some embodiments of the present invention, the ratio of the total mole of 2-bromo-3-(2-butoxyethyl)thiophene and 2-bromo-3-hexylthiophene to the mole of the inorganic base is 1-1.5:1-1.5.

[0028] In some embodiments of the present invention, the ratio of the total mole of 2-bromo-3-(2-butoxyethyl)thiophene and 2-bromo-3-hexylthiophene to the mole of the organic acid is 2.5-4.5:1.

[0029] In some embodiments of the present invention, after the reaction is completed, a purification step is further included.

[0030] Another object of the present invention is to provide the use of the long ether chain thiophene copolymer or the long ether chain thiophene copolymer prepared by the preparation method of the long ether chain thiophene copolymer in the preparation of perovskite solar cells.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] (1) The molecular structure of the long ether chain thiophene copolymer provided by the present invention contains a 3-(2-butoxyethyl)thiophene segment, which can effectively improve the problem of poor physical contact between P3HT and the perovskite interface, reduce voltage and current losses, and thus effectively improve the energy conversion efficiency of perovskite solar cells.

[0033] (2) The long ether chain thiophene copolymer provided by the present invention has an irregular structure, high regularity and high molecular weight, which can effectively inhibit the aggregation of the long ether chain thiophene copolymer and improve the solubility and processability of the material in the solvent.

[0034] (3) The long ether chain thiophene copolymer provided by the present invention contains a long chain and an ether bond structure in its molecular chain, which can improve the solubility of the long ether chain thiophene copolymer in chlorobenzene and / or dichlorobenzene. The long ether chain thiophene copolymer provided by the present invention has broad application prospects in the fields of solar cells, organic transistors, electrochromic devices, chemical sensors, electromagnetic shielding materials, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is the H-NMR spectrum of the long ether chain thiophene copolymer L1 provided in Example 1.

[0036] Figure 2 This is the H NMR spectrum of the long ether chain thiophene copolymer L2 provided in Example 2.

[0037] Figure 3 This is the H NMR spectrum of the long ether chain thiophene copolymer L3 provided in Example 3.

[0038] Figure 4 This is the H NMR spectrum of the long ether chain thiophene copolymer L4 provided in Example 4.

[0039] Figure 5 This is the H NMR spectrum of the long ether chain thiophene copolymer L5 provided in Example 5. DETAILED DESCRIPTION

[0040] The following will clearly and completely describe the concept of the present invention and the technical effects produced in combination with the embodiments, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by technicians in this field without creative work are all within the scope of protection of the present invention. The test methods used in the embodiments are all conventional methods unless otherwise specified; the materials, reagents, etc. used, unless otherwise specified, can all be reagents and materials obtained from commercial channels.

[0041] In the following examples and comparative examples, the content of 3-(2-butoxyethyl)thiophene segments in the long ether chain thiophene copolymer was determined by nuclear magnetic resonance, the long ether chain thiophene copolymer was dissolved in deuterated chloroform, TMS was used as the internal standard, and the measurement temperature was 25°C. The molecular weight or degree of polymerization of the long ether chain thiophene copolymer was determined by gel permeation chromatography (GPC) with THF mobile phase. Among them, HT and HT values ​​represent isotacticity, and PDI represents molecular weight distribution index;

[0042] The structural formula of 2-bromo-3-(2-butoxyethyl)thiophene is shown below:

[0043] .

[0044] Example 1

[0045] This embodiment provides a long ether chain thiophene copolymer L1, and the synthesis method thereof is as follows:

[0046] Under nitrogen atmosphere, 2-bromo-3-(2-butoxyethyl)thiophene (0.025mmol), 2-bromo-3-hexylthiophene (0.475mmol), potassium carbonate (0.75mmol), diimine palladium catalyst C1 (0.25mmol%), pivalic acid (0.15mmol), and dimethylacetamide (4mL) were reacted at 100°C for 24h, and precipitated in methanol to obtain a long ether chain thiophene copolymer L1 with a yield of 66%, an HT value of 91%, a PDI of 2.61, a number average molecular weight Mn of 8.9KDa, and a molar percentage of 3-(2-butoxyethyl)thiophene segments in the long ether chain thiophene copolymer segments of 4.7%, that is, a copolymerization degree of 4.7mmol; the structures of the diimine palladium catalyst C1 and the random long ether chain thiophene copolymer L1 are shown below:

[0047]

[0048] Among them, x=4.7mmol%, y=95.3mmol%.

[0049] Example 2

[0050] This embodiment provides a long ether chain thiophene copolymer L2, and its synthesis method is as follows:

[0051] Under nitrogen atmosphere, 2-bromo-3-(2-butoxyethyl)thiophene (0.05mmol), 2-bromo-3-hexylthiophene (0.45mmol), potassium carbonate (0.75mmol), diimine palladium catalyst C1 (0.25mmol%), pivalic acid (0.15mmol), dimethylacetamide (4mL) were reacted at 100°C for 24h, and precipitated in methanol to obtain a long ether chain thiophene copolymer L2 with a yield of 48%, an HT value of 92%, a PDI of 2.67, a number average molecular weight Mn of 6.5KDa, and a molar percentage of 3-(2-butoxyethyl)thiophene segments in the long ether chain thiophene copolymer segments of 8.3%, that is, a copolymerization degree of 8.3mmol; the structures of the diimine palladium catalyst C1 and the random long ether chain thiophene copolymer L2 are shown below:

[0052]

[0053] Among them, x=8.3mmol%, y=91.7mmol%.

[0054] Example 3

[0055] This embodiment provides a long ether chain thiophene copolymer L3, and its synthesis method is as follows:

[0056] Under nitrogen atmosphere, 2-bromo-3-(2-butoxyethyl)thiophene (0.075mmol), 2-bromo-3-hexylthiophene (0.425mmol), potassium carbonate (0.75mmol), diimine palladium catalyst C1 (0.25mmol%), pivalic acid (0.15mmol), dimethylacetamide (4mL) were reacted at 100°C for 24h, and precipitated in methanol to obtain a long ether chain thiophene copolymer L3 with a yield of 63%, an HT value of 90%, a PDI of 3.05, a number average molecular weight Mn of 7.2KDa, and a molar percentage of 3-(2-butoxyethyl)thiophene segments in the long ether chain thiophene copolymer segments of 12.5%, that is, a copolymerization degree of 12.5mmol; the structures of the diimine palladium catalyst C1 and the random long ether chain thiophene copolymer L3 are shown as follows:

[0057]

[0058] Among them, x=12.5mmol%, y=87.5mmol%.

[0059] Example 4

[0060] This embodiment provides a long ether chain thiophene copolymer L4, and its synthesis method is as follows:

[0061] Under nitrogen atmosphere, 2-bromo-3-(2-butoxyethyl)thiophene (0.1mmol), 2-bromo-3-hexylthiophene (0.4mmol), potassium carbonate (0.75mmol), diimine palladium catalyst C1 (0.25mmol%), pivalic acid (0.15mmol), dimethylacetamide (4mL) were reacted at 100°C for 24h, and precipitated in methanol to obtain a long ether chain thiophene copolymer L4 with a yield of 50%, a HT value of 92%, a PDI of 2.89, a number average molecular weight Mn of 7.0KDa, and a molar percentage of 3-(2-butoxyethyl)thiophene segments in the long ether chain thiophene copolymer segments of 16%, that is, a copolymerization degree of 16mmol; the structures of the diimine palladium catalyst C1 and the random long ether chain thiophene copolymer L4 are shown below:

[0062]

[0063] Among them, x=16mmol%, y=84mmol%.

[0064] Example 5

[0065] This embodiment provides a long ether chain thiophene copolymer L5, and its synthesis method is as follows:

[0066] Under nitrogen atmosphere, 2-bromo-3-(2-butoxyethyl)thiophene (0.125mmol), 2-bromo-3-hexylthiophene (0.4mmol), potassium carbonate (0.375mmol), diimine palladium catalyst C1 (0.25mmol%), pivalic acid (0.15mmol), dimethylacetamide (4mL) were reacted at 100°C for 24h, and precipitated in methanol to obtain a long ether chain thiophene copolymer L5 with a yield of 49%, an HT value of 94%, a PDI of 3.06, a number average molecular weight Mn of 7.5KDa, and a molar percentage of 3-(2-butoxyethyl)thiophene chain segments in the long ether chain thiophene copolymer segment of 20%, that is, a copolymerization degree of 20mmol; the structures of the diimine palladium catalyst C1 and the random long ether chain thiophene copolymer L5 are shown as follows:

[0067]

[0068] Among them, x=20mmol%, y=80mmol%.

[0069] Example 6

[0070] This embodiment provides a pin-type perovskite solar cell, the specific cell structure is ITO / long ether chain thiophene copolymer / perovskite active layer / PCBM / BCP / Ag, and the specific implementation steps are as follows:

[0071] (1) Cleaning of the transparent substrate layer: First, take out the ITO transparent conductive glass, tear off the plastic protective film on the surface, and first use detergent to gently wipe the surface oil and dirt, and then ultrasonically clean it in a 0.2wt% detergent aqueous solution, deionized water, and isopropanol for 15 minutes respectively. Finally, use nitrogen to blow dry the isopropanol on the ITO surface and put it in a box for later use.

[0072] (2) Deposition of hole transport layer: The long ether chain thiophene copolymer of Example 1 was prepared into a precursor solution of 0.2 mg / mL, and the solvent was chlorobenzene. The cleaned ITO was first placed in an ultraviolet ozone cleaner for surface hydrophilic treatment, and then the precursor solution was sucked out with a pipette and evenly covered on the ITO surface. The solvent was dried by spin coating (500 rpm / min, 3 s; 3000 rpm / min, 20 s).

[0073] (3) Preparation of wetting layer: The purchased aluminum oxide nanoparticle (<50 nm) dispersion (20%) was mixed with isopropanol at a volume ratio of 1:50 (aluminum oxide dispersion: isopropanol) to prepare an aluminum oxide precursor solution. The prepared aluminum oxide precursor solution was then aspirated with a pipette and evenly covered on the surface of the hole transport layer. The solvent was dried by spin coating (100 rpm / min, 3 s; 5000 rpm / min, 20 s).

[0074] (4) Preparation of perovskite active layer: The FAPbI3 system perovskite precursor solution (1000 rpm / min, 3s; 5000 rpm / min, 30s, 100 μL chlorobenzene was added as anti-solvent at 21s) was aspirated with a pipette and evenly covered on the surface of the wetting layer to form a perovskite active layer, and then annealed on a hot stage at 100°C for 30-60 min.

[0075] (5) Deposition of electron transport layer: Weigh 20 mg of PCBM and add 1 mL of chlorobenzene to prepare the precursor solution of the electron transport layer. The electron transport layer precursor solution was deposited on the surface of the perovskite active layer by spin coating (500 rpm / min, 3 s; 2500 rpm / min, 20 s).

[0076] (6) Deposition of hole blocking layer: 8 mg of BCP was weighed and 16 mL of isopropanol was added to prepare a precursor solution. The prepared precursor solution was then aspirated with a pipette and evenly covered on the surface of the hole blocking layer. The solvent was dried by spin coating (100 rpm / min, 3 s; 5000 rpm / min, 20 s).

[0077] (7) Deposition of metal electrode layer: A 100 nm thick Ag film was thermally evaporated under high vacuum at an evaporation rate of 0.3 Å / s for 20 nm and then deposited on the surface of the hole blocking layer at 1 Å / s to a thickness of 100 nm.

[0078] Example 7

[0079] This embodiment provides a pin-type perovskite solar cell, which differs from Embodiment 6 in that the "long ether chain thiophene copolymer of Embodiment 1" in step (2) of Embodiment 6 is replaced with "long ether chain thiophene copolymer of Embodiment 2" to obtain the pin-type perovskite solar cell of Embodiment 7.

[0080] Example 8

[0081] This embodiment provides a pin-type perovskite solar cell, which differs from Embodiment 6 in that the "long ether chain thiophene copolymer of Embodiment 1" in step (2) of Embodiment 6 is replaced with "long ether chain thiophene copolymer of Embodiment 3" to obtain the pin-type perovskite solar cell of Embodiment 8.

[0082] Example 9

[0083] This embodiment provides a pin-type perovskite solar cell, which differs from Embodiment 6 in that the "long ether chain thiophene copolymer of Embodiment 1" in step (2) of Embodiment 6 is replaced with "long ether chain thiophene copolymer of Embodiment 4", thereby obtaining the pin-type perovskite solar cell of Embodiment 9.

[0084] Example 10

[0085] This embodiment provides a pin-type perovskite solar cell, which differs from embodiment 6 in that the "long ether chain thiophene copolymer of embodiment 1" in step (2) of embodiment 6 is replaced with "long ether chain thiophene copolymer of embodiment 5" to obtain the pin-type perovskite solar cell of embodiment 10.

[0086] The performance of the pin-type perovskite solar cells of Examples 6 to 10 was tested. The test method is as follows and the results are shown in Table 1.

[0087] (1) JV characteristic curve: The JV characteristic curve of the device was measured using a Keithley 2440 light source under a simulated AM1.5G spectrum.

[0088] The light intensity was calibrated using a solar simulator (Newport, 91160) from NREL using a standard silicon solar cell device. The effective measurement area was 0.07 cm 2 , under reverse and forward bias scans, the scan rate was 100mV / s and the bias range was from -0.2V to 1.2V.

[0089] Table 1. Performance of perovskite solar cells of Examples 6 to 10.

[0090] sample Voc(V) <![CDATA[Jsc(mA / cm 2 )]]> (%) (%) Example 6 1.05 23.57 72.59 17.96 Example 7 1.03 23.61 72.62 17.66 Example 8 1.04 22.34 69.34 16.11 Example 9 1.06 23.73 73.13 18.39 Example 10 1.07 23.49 73.08 18.37

[0091] As can be seen from Table 1, the long ether chain thiophene copolymers prepared in Examples 1 to 5 of the present invention have high Voc, high Jsc, and high FF for preparing perovskite solar cells, thereby obtaining a high PCE value.

[0092] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A long ether chain thiophene copolymer, characterized in that: The long ether chain thiophene copolymer is a copolymer of 3-hexylthiophene and 3-(2-butoxyethyl)thiophene, wherein the molar percentage of the 3-(2-butoxyethyl)thiophene segment in the long ether chain thiophene copolymer segment is 4.7% to 20%.

2. The long ether chain thiophene copolymer according to claim 1, characterized in that: The molar percentage of the 3-(2-butoxyethyl)thiophene chain segment to the long ether chain thiophene copolymer chain segment is 4.7% to 8.3%.

3. The long ether chain thiophene copolymer according to claim 1, characterized in that: The molar percentage of the 3-(2-butoxyethyl)thiophene chain segment to the long ether chain thiophene copolymer chain segment is 16% to 20%.

4. The long ether chain thiophene copolymer according to claim 1, characterized in that: The long ether chain thiophene copolymer is a random copolymer.

5. The long ether chain thiophene copolymer according to claim 1, characterized in that: The structure of the long ether chain thiophene copolymer is shown in formula (I): Formula (I) Wherein, the number average molecular weight of the long ether chain thiophene copolymer is 6.5~8.9KDa.

6. The long ether chain thiophene copolymer according to claim 1, characterized in that: The long ether chain thiophene copolymer has an HT value of ≥90% and a PDI of ≥2.

5.

7. A method for preparing a long ether chain thiophene copolymer, characterized in that: The steps include: Under the catalysis of a palladium catalyst, 2-bromo-3-(2-butoxyethyl)thiophene and 2-bromo-3-hexylthiophene react to obtain the long ether chain thiophene copolymer according to any one of claims 1 to 6.

8. The method for preparing a long ether chain thiophene copolymer according to claim 7, characterized in that: The palladium catalyst is selected from diimine palladium catalyst; and / or, the molar ratio of 2-bromo-3-(2-butoxyethyl)thiophene to 2-bromo-3-hexylthiophene is 1-5:15-19; And / or, the ratio of the total mole of 2-bromo-3-(2-butoxyethyl)thiophene and 2-bromo-3-hexylthiophene to the mole of the palladium catalyst is 1:0.001-0.01; And / or, the reaction further contains an inorganic base, an organic acid and a solvent; And / or, the reaction temperature is 80-120° C. and the reaction time is 12-36 hours.

9. The method for preparing a long ether chain thiophene copolymer according to claim 8, characterized in that: The inorganic base includes at least one of potassium carbonate and sodium carbonate; And / or, the organic acid includes at least one of pivalic acid and caproic acid; and / or, the solvent comprises N,N-dimethylacetamide; and / or, the ratio of the total mole of 2-bromo-3-(2-butoxyethyl)thiophene and 2-bromo-3-hexylthiophene to the mole of the inorganic base is 1-1.5:1-1.5; And / or, the ratio of the total mole of 2-bromo-3-(2-butoxyethyl)thiophene and 2-bromo-3-hexylthiophene to the mole of the organic acid is 2.5-4.5:

1.

10. Use of the long ether chain thiophene copolymer according to any one of claims 1 to 6 or the long ether chain thiophene copolymer prepared by the method for preparing the long ether chain thiophene copolymer according to any one of claims 7 to 9 in preparing perovskite solar cells.

Citation Information

Patent Citations

  • Soluble thiophene copolymer and preparation method and application thereof

    CN110218298A

  • Catalyst for catalytic preparation of polythiophene and P3HT material

    CN117105990A

  • Polythiophene electronic devices

    US20080142788A1